Chopin w tłumaczeniu Michała Bristigera w „De Musica” na podstawie książki Luciena Bourguèsa i Alexandre’a Denéréaza - Poniatowska, Irena (Res Facta Nova, 2021)
Michał Bristiger took a fragment from the book La musique et la vie interieure by L. Bourguès and A. Denéréaz published in 1921, translated it under the title Chopin, and published it in “De musica” vol. I–III in 2006. The authors, who represented energo-psychological research approach, a theory that was being promoted at that time (H. Mersman, Angewandte Musikaesthetik, 1926 and E. Kurth, Musikpsychologie), provided a psychological and musical interpretation of Chopin’s melodics (linked to harmony and texture), and their significance in the integration of form. They distinguish such categories as c o n t i n u i t y and p e n d u l u m m o t i o n, or undulating, wave-like movements that expand and lead to a culmination, the outflow from which takes the form of, for example, a gliding flight, “plané”. They describe Chopin’s imagination as ballistic. Previous research had focused exclusively on the microstructures of melody, on characteristic intervals, typical phrases, expressive gestures, and not on the flow, on the impulses in the creation of contrast, on the rising and falling of the melodic line, and for this reason the Chopin chapter in this book remains a source of inspiration to this day.